Analysis of the Context of Coping Mechanisms - Rohmah, Ulfia Nur; Amalia, Putri; Sari, Illa Purnama; Muslim, Muslim; Yasmin, Apriliantini; Wisma, Nur (Scidacplus, 2024)
Coping mechanisms are methods or steps used by individuals to solve problems, adapt, tolerate, accept, and overcome changes that occur in their lives in situations that threaten or exceed their psychological and behavioral abilities. They indicate a major part of dealing with one's stress. Come through interventions and techniques. This research aims to examine and analyze the command regarding coping mechanisms in Indonesia in the last decade to show its novelty. This Content analysis is used as an analysis method. The examples used are articles published on Google Scholar and Research Gate. Data searches are based on reviewing research titles, techniques, and results. The research results show that coping mechanisms affect personal, academic, professional, nursing, athletic, and national defense. Methodologically, descriptive analysis techniques and univariate data are the methods most widely used to determine relationships. It is desired that research on coping mechanisms can help future researchers study coping mechanisms with other psychological aspects using different research methods.